Revitalisasi Karakter Religius melalui Metode Active Learning di Raudlatul Athfal Khodijah Nganjuk - Makhmudah, Siti (Kartika: Jurnal Studi Keislaman, 2024)
Character education is the key for every generation, where each generation has its own challenges. The development of increasingly digitalized technology is one of the many challenges of this generation and beyond. For this reason, strengthening religious character is one of the keys to strengthening the character of this and future generations because every person in a generation has the nature of being a religious person. This research aims to find strategies for improving religious character through active learning methods in early childhood at RA Khodijah Nganjuk. This research uses classroom action research methods. The research subjects were teachers and students of group A RA Khodijah Nganjuk. Based on the results of this research, it was found that the active learning method improved students' religious character. It is supported by other methods, namely the teacher's example in behavior and tolerance.